The Study Of "Korosanai" Among The Siddha Physicians In Jaffna MOH Division - Thayalini, T.; Lakshinevetha, G.; Vidhya, M.P. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
Siddha medicine is one of the medical systems of Indigenous medical system. Korosanai is classified under the Thathuvakupu in siddha medicine.It is used as one of the ingredient in many siddha drugs in the Treatment of Respiratory system, Gastro intestinalsystem (GIT) and skin in childrens. It has Expectorant, cooling, antispasmodic and Laxative properties. Korosanaimathirai,mukkudumathirai, Kasthurimathirai are drugs contains korosanai. The aim of study was to identify the drugs which are containkorosanai and usage by siddha physician in Jaffna MOHdivision. The study was conducted in January- August 2015 in Jaffna MOHdivision. Details of Physician were obtained from Divisional secretary office Jaffna and Nallur. 18(14 Trained physicians, 3 Traditional and 1 Trained with traditional knowledge) siddha physicians are practicing Siddha medicine in Jaffna MOH division. All the physicians were interviewed by the researcher using self administrative questionnaire which was prepared based on the objectives. All the physicians used different name of the drugs which are contain korosanai as one of the ingredient. They are 17 (94%) Thakkalichchattukorosanai, 3(17%) Palarukkanakorosanai,3 (17%) Pakalillaichattukorosanai, 2 (11%) Kiranthivayukorosani, Kakkanavanillaichcharukorosanai, Mukkudumathirai, Kovaiillaichchattukorosanai, Vettillichchatukorosani, and Korosanikulikai. Thakkalichattukorosani is used for fever with Respiratory disorders and skin conditions( karappan and Kiranthi) by 94% of the physicians. This drug was prepared by the Municipal council Jaffna and it was distributed to the branches of the 9 dispensaries.72% of physicianspriscribedkorosani drugs forfever, 61% for respiratory, 33% for skin, and 38% for GIT problems in under 5 years children. One Traditional physician used Periyakorosanai, Korosanaimiruththiyathi, Suvasakkulikai, Kolaisannikulikai Rasangam, Aamaiyoddukorosanai Balasanjeevi and Punukuellathi These drugs are used for Mantham(diarrhea), kasam (cough)and Thoivu ( Bronchial asthma). One physician used porumalkulikai for indigestion due to feeding of artificial milk. Drugs containing korosani are used by the physicians in different names and ingredients for fever,respiratory,skin, and GIT problems in Jaffna district.
Keywords: korosanai; Siddha physicians; Jaffna MOH division